Nutritional composition of swiftlets (Aerodramus fuciphagus) faeces for future usage - Azizon Abdullah; Wan Zahari Mohamed; Ali Saifudin; M.Bohari Jusoh (2012)
A total of 104 samples of Swiftlet faeces were collected from various districts in Kelantan (n:55) and Terengganu (n:49). The samples were analysed for dry matter (DM), crude protein (CP), ether extract (EE), Ash, Calcium (Ca) and Phosphorus (P). The overall mean concentrations of organic matter (OM), CP, Ash, Ca and P from those samples were 72.25 %, 68.23 %, 8.84%, 1.01% and 1.19% respectively while the mean nitrate (NO3) content was estimated 48.33%. There were no significant differences (P>0.05) between districts in the OM, Ca and P content. However, significant differences (P<0.05) were observed in the CP, NO3 and ash content between districts. The potential of swiftlet faeces as the source of superior quality fertilizer and other usage are highlighted.